2021
DOI: 10.1177/00220345211054744
|View full text |Cite
|
Sign up to set email alerts
|

Ckip-1 MediatesP. gingivalis–Suppressed Cementoblast Mineralization

Abstract: Porphyromonas gingivalis is responsible for the destruction of cementum in patients with periodontitis and periapical periodontitis. However, research about the effects of P. gingivalis on cementoblast mineralization and the underlying mechanism is still lacking. Casein kinase 2 interacting protein 1 (Ckip-1) is a scaffold protein that interacts with various proteins and signals to regulate different cell functions, such as cell morphology, apoptosis, and differentiation. In this study, we verified the suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…It has been previously found that the MAPK pathway contributes to cementum mineralization. [25][26][27] Moreover, the activation of ERK by CoCl 2 -induced hypoxia has been reported in vitro and in vivo, including in OCCM-30 cells. 13,24 Thus, we explored whether the MAPK pathway regulates the mineralization and mitochondria biogenesis of upregulation, including the MAPK, insulin, mTOR, and WNT pathways, which have all been identified as inducers of mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been previously found that the MAPK pathway contributes to cementum mineralization. [25][26][27] Moreover, the activation of ERK by CoCl 2 -induced hypoxia has been reported in vitro and in vivo, including in OCCM-30 cells. 13,24 Thus, we explored whether the MAPK pathway regulates the mineralization and mitochondria biogenesis of upregulation, including the MAPK, insulin, mTOR, and WNT pathways, which have all been identified as inducers of mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies have demonstrated that the activation of the p38 mitogen-activated protein kinase (MAPK) pathway enhanced the activity of PGC-1α, 23 and that hypoxia induction led to ERK activation in vitro and in vivo. 13,24 Moreover, it has been proven that the MAPK pathway is essential for cementoblast mineralization; [25][26][27] we, therefore, set out to explore whether the MAPK signaling pathway was involved in this process.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several signaling pathways have been identified as being involved in cementoblast mineralization, such as WNT, 36 Hedgehog, 37 Notch, 38 BMP, 39 TGF-β, 40 Akt, 4,5 MAPKs, 4,5 and other pathways. 41 As an important part of the MAPKs pathway, the p38 signaling was shown to regulate cementoblast mineralization positively, 4,5,41 though activated p38 signaling was also detected in cementoblasts induced with TNF-α, a suppressor of cementoblast mineralization. 42 Strengthened p38 signaling was observed in M2 macrophage-associated groups when compared with their own M0 macrophage-associated controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the oral cavity, activation of NOD2 by muramyl dipeptide (MDP) can upregulate expression of proinflammatory mediators and cytokines, thereby enhancing the immune response of dental pulp to pathogens [ 26 ]. Porphyromonas gingivalis is responsible for destruction of cementum and progression of PP in general [ 27 , 28 ].Upregulation of NOD2 expression may be due to NOD2 activation by MDP in P. gingivalis , which participates in the progression of periapical inflammation. Analyses of functional enrichment of DEGs using the GO database indicated that DEGs were enriched mainly in regulation of the cellular response to lipopolysaccharide (BP), transmembrane receptor protein tyrosine kinase (MF), and intracellular membrane-bounded organelle (CC).…”
Section: Discussionmentioning
confidence: 99%
“…In the oral cavity, activation of NOD2 by muramyl dipeptide (MDP) can upregulate expression of proinflammatory mediators and cytokines, thereby enhancing the immune response of dental pulp to pathogens [26]. Porphyromonas gingivalisis responsible for destruction of cementum and progression of PP in general [27,28].Upregulation of NOD2 expression may be due to NOD2 activation by MDP in Inflammatory progression is closely related to bone loss. Yuan and colleagues showed thatNOD2-deficiency in rats led to aggravation of inflammatory processes associated with atherosclerosis and periodontitis.…”
Section: Discussionmentioning
confidence: 99%